Effects of the training and of the maintenance of physical activity in four sedentary healthy elderly (Fisioterapia e Pesquisa, 2001)
This article intends a comprehensive follow-up of four, elderly people, previously sedentary, who participated in a group of physical training (general exercises or walking) with significantly different outcomes. Two of them underwent a training of general exercises during four months. One of those abandoned and another maintained the exercising practice for one year. Other two elderly underwent a walking training during four months. Similarly one abandoned and the other maintained the walking routine for one year. The muscleskeletal, neuromuscular, cardiovascular and respiratory functions, and body composition were studied and compared. We found that all subjects improved the physical performance with training. The improvement depended upon the type of training and it was preserved or enhanced with the maintenance of exercising practice during the period of one year. Boths the subjects who have dropped out the training did not achived that good results.